Study of the anisotropic effects of hydrogen on the subsurface mechanical behavior of nickel single crystal by nanoindentation - Y. Ben Jedidia; S.P. Murugan; X. Feaugas; A. Oudriss (Materials & Design, 2025)
Hydrogen ingress can significantly alter subsurface mechanical properties, often in a different manner than in the bulk. In this work, we investigate the effect of hydrogen on the subsurface mechanical behavior of face-centered cubic nickel single crystals using nanoindentation. Four crystallographic orientations (100), (110), (111), and (219) were examined before and after electrochemical hydrogen charging, with particular attention paid to surface preparation. The mechanical response is analyzed in terms of the nanoindentation reduced modulus (using the Hertz model), pop-in load and depth, and hardness. Our results show a reduction in elastic modulus that depends on crystallographic orientation and is associated with vacancy formation and potential hydride phases. Hydrogen alters the anisotropy of incipient plasticity through elastic shielding and enhanced dislocation pinning. The observed trends, orientation-dependent softening of modulus, depth-dependent pop-in behavior, and changes in critical shear stress are explained by the competing effects of softening (via vacancy and hydride formation) and hardening (via dislocation pinning), thus offering new insights into hydrogen-induced mechanical anisotropy in nickel.